Rare Benign cystic teratoma in the parotid gland - Gharaibeh, Mahmoud M.; Alwadiya, Ahmed; Gharaibeh, Ahmad; Hammad, Hdua (European Journal of Clinical and Experimental Medicine, 2020)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. A teratoma is a tumor developed of several different types of tissue, like hair, muscle, teeth or bone. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. Mature benign cystic teratomas are very rare in the salivary glands and just few cases were reported. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. A 13 years old female was presented to our dental clinic of Princes Basma Hospital in Irbid in north of Jordan, with a painless, insidious progressive swelling in left parotid region without any significant family and personal history. Parents were cancer phobic and nervous from the condition of their daughter, they were very confused. There was no pain or any history of trauma. It was present just inferior to left ear cartilage. The mass was of size 3x3cm, non-tender, fixed, soft to firm in consistency, having smooth surface. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Teratoma in parotid region is an extremely rare entity. Lack of any pathognomonic feature, it is hard to diagnose preoperatively. Lumpectomy is advisable to remove the mass because the risk of damaging facial nerve in young patients and recurrence is rare. A definitive diagnosis is achieved after the histopathological study. Teratoma should be kept in account while evaluating a case of a soft tissue mass of parotid gland as a differential diagnosis.